COMPUTERIZED ACCOUNTING TRAINING WITH LOCAL SOFTWARE TO FACILITATE FINANCIAL REPORTING FOR BUMDES MANAGEMENT IN CISAAT VILLAGE, SUBANG (WEST JAVA) - Achmad Fauzi; Ati Sumiati; Santi Susanti; Sri Zulaihati; Dwi Kismayanti Respati; Mardi Mardi; Dwi Handarini; Wawan Aprianto (Yayasan Education and Social Center, 2022)
One of the government programs to develop the economy in rural areas is the establishment of village-owned enterprises (BUMDes). In carrying out its operations, BUMDes often experience obstacles, one of which is the obstacle in making BUMDes financial reports. This activity is one of the efforts to solve the problem of slow financial reporting and the inability of BUMDes administrators to provide accurate financial information to their stakeholders. Through this activity, it is hoped that the bumdes administrators can make real and completed financial reports on time before the Annual Membership Meeting is held by introducing and training how to make financial reports using local software-based accounting computers that have been created by the nation's children, namely Zahir Accounting software